2010
DOI: 10.2466/06.10.11.13.15.25.pms.111.4.178-186
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Fitness Training on Reaction Time in Youth with Intellectual Disabilities

Abstract: The purpose of this study was to assess whether reaction time in persons with intellectual disabilities can be improved with an exercise program. 50 children and adolescents (M age = 14.7 yr., SD = 1.4, range = 11-18) with mild intellectual disability without Downs syndrome were randomly divided into control (20 boys, 5 girls) and experimental (19 boys, 6 girls) groups. The experimental group participated in a structured physical fitness program for 12 weeks. Reaction time was assessed at baseline and after 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 15 publications
2
26
0
1
Order By: Relevance
“…These results are in agreement with previous findings, although these studies used different methodology (Un & Erbahçeci, 2001;Yildirim, Erbahceci, Ergun, Pitetti, & Beets, 2010). Particularly, active individuals with ID who were playing basketball showed shorter reaction time compared to non active peers when responding to an auditory or light stimulus via a button-press using the index finger of their dominant hand (Un & Erbahçeci, 2001).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results are in agreement with previous findings, although these studies used different methodology (Un & Erbahçeci, 2001;Yildirim, Erbahceci, Ergun, Pitetti, & Beets, 2010). Particularly, active individuals with ID who were playing basketball showed shorter reaction time compared to non active peers when responding to an auditory or light stimulus via a button-press using the index finger of their dominant hand (Un & Erbahçeci, 2001).…”
Section: Discussionsupporting
confidence: 95%
“…Particularly, active individuals with ID who were playing basketball showed shorter reaction time compared to non active peers when responding to an auditory or light stimulus via a button-press using the index finger of their dominant hand (Un & Erbahçeci, 2001). A more recent study that used the same methodology found that adolescents with ID who participated in a twelve week structured physical fitness program improved their reaction time to visual and auditory stimuli (Yildirim et al, 2010). To our knowledge, only one study examined the effects of exercise on reaction time in young individuals with ID (Song & An, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…There is evidence that children with autism have difficulty understanding the goals of physical exercise [50], increasing further the challenge of ongoing involvement with fitness programmes. The research that does exist on helping children with autism take more exercise and improve their physical fitness tends to be focussed upon jogging and swimming [45, 51], with modelling and physical guidance generally being the method of instruction [45].…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient physical activity further limits the person's autonomy in activities of daily living (Piek, Dawson, Smith and Gasson, 2008) which negatively affects their health (Carbo-Carrete, Guardia-Olmos and Gine 2016). The sedentary lifestyle results in lower balance performance, overall motor functioning (Giagazoglou et al, 2012;Horvat, Ramsey, Amestoy and Croce, 2003;Lin et al, 2010;Yildirim, Erbahceci, Ergun, Pitetti and Beets, 2010), and motor impairments among inactive individuals with intellectual disabilities (Carmeli, Bar-Yossef, Ariav, Levy and Liebermann, 2008). Motor deficits are commonly reported in persons with intellectual disabilities since this condition can affect cognitive and motor functions (Cleaver, Hunter and Ouellette-Kuntz, 2009;Hartman, Houwen, Scherder and Visscher, 2010;Vuijk, Hartman, Scherder and Visscher, 2010).…”
Section: Introductionmentioning
confidence: 99%